SOSIALISASI MENGENAI EDUKASI PENCEGAHAN DIARE PADA SISWA SD NEGERI 12 PURWODADI - Gigih Kenanga Sari; Wendy Mayasari Kalalo; Maranatha Cicilia (LPPM AN Nuur, 2023)
Background: Information regarding education on preventing diarrheal diseases in students. This information is provided in the form of outreach activities (counseling) to the community. It is hoped that this educational and outreach activity will provide an overview of behavior in preventing diarrhea in young students, as well as efforts to prevent diarrhea in children regarding hand washing habits and preventing diarrhea regarding water use. Method: outreach to students at SD Negeri 12 Purwodadi, the majority of whom do not understand how to educate about preventing diarrhea. Results: There were 21 students in 1 class who understood the importance of washing hands and preventing diarrhea for students at SD Negeri 12 Purwodadi. Conclusion: compliance with student awareness about the importance of washing hands and preventing diarrhea among students at SD Negeri 12 Purwodadi.